DAMPAK KINERJA BAURAN PEMASARAN TERHADAP KEPUTUSAN KULIAH CALON MAHASISWA POLITEKNIK X CIMAHI - Suharyanto Suharyanto (Jurnal Manajemen Industri dan Logistik, 2018)
The higher education service providing become one of business which needs hard working especially in student recruitment. The alumni of vocational high school (SMK) and general high school (SMA) who will to continue study in higher education, can become to be opportunities. To keep these, the higher education institutions have to compete with the others, applying  right marketing mix. This research article shows the marketing mix performance  effects to student candidates decision to study in Polytechnic X Cimahi. The research population are student canditates in academic year of 2017, and 50 samples were got simple randomly. The effects of marketing communication mix and marketing mix to student decision analysed using simple linier regression model. The research result shows that variables of  marketing mix performance  gives medium effects 61,4% to student decision, and 38,6% effected by others. The linier regression model constructed is Y= 0,690X +1,248.